The 2-Pebbling Property of the Middle Graph of Fan Graphs - Yongsheng Ye; Fang Liu; Caixia Shi (Journal of Applied Mathematics)
A pebbling move on a graph G consists of taking two pebbles off one vertex and placing one pebble on an adjacent vertex. The pebbling number of a connected graph G, denoted by f(G), is the least n such that any distribution of n pebbles on G allows one pebble to be moved to any specified but arbitrary vertex by a sequence of pebbling moves. This paper determines the pebbling numbers and the 2-pebbling property of the middle graph of fan graphs.